Barriers to Early Mobility of Hospitalized General Medicine Patients. (April 2015) - Hoyer, Erik H.; Brotman, Daniel J.; Chan, Kitty S.; Needham, Dale M.
ABSTRACT Objective Functional status decline commonly accompanies hospitalization making patients vulnerable to complications. Such decline can be mitigated through hospital-based early mobility programs. Success in implementing patient mobility quality improvement processes requires evaluating providers' knowledge, attitudes, and behaviors. Design A cross-sectional, self-administered survey in two different hospital settings was completed by 120 nurses and physical and occupational therapists (rehabilitation therapists, 38; nurses, 82) from six general medicine units. The survey was developed using published guidelines, literature review, and provider meetings and refined through pilot testing. Psychometric properties were assessed, and regression analyses were conducted to examine barriers to early mobility by hospital site, provider discipline, and years of experience. Results Internal consistency reliability, item consistency, and discriminant validity psychometric characteristics were acceptable. In multivariable regression analysis, overall perceived barriers were similar between the two hospitals (P = 0.25) and significantly higher for staff with less experience (P = 0.02) and for nurses vs. rehabilitation therapists (P < 0.001).The survey identified specific barriers common to both nurses and rehabilitation therapists and other barriers that were discipline specific. Conclusions This novel survey identified important barriers to mobilizing medical inpatients that were similar across two hospital settings. These results can assist with the implementation of quality improvement projects for increasing early hospital-based patient mobility.